Integrated biological and behavioral surveillance survey among wives of migrant laborers in four districts of far-western regions of Nepal: round I. - Tuladhar,Sidhartha Man (2008)
SUMMARY: This report presents the findings of the first round of the Integrated Biological and Behavioral Surveillance Survey (IBBS) of wives of migrant laborers in West to Far-Western Nepal. This study is based on surveys of 400 spouses of those migrant laborers in the four districts of Achham, Doti, Kanchanpur, and Kailali who temporarily migrate or had migrated to India to work as laborers. The survey was conducted among the wives or widows of current or ex- labor migrants to India aged 16 years or over, whose spouse had spent at least three months in India and who had retuned to Nepal at least once in the last three years. The survey measured the prevalence of HIV among the study population. It also looked at multiple factors associated with risks for HIV infection, including condom use, sexual behavior, knowledge of HIV/AIDS and sexually transmitted infections (STIs), STI treatment history, exposure to HIV/AIDS awareness messages, and alcohol/drug use habits. Study Methodology Two stage cluster sampling was followed to draw the sample of 400 wives of migrant laborers. The first stage was the development of the sampling frame and selection of the cluster and the second stage was selection of 400 wives of migrant laborers from the selected cluster. Maps were developed to list the areas where wives of migrant laborers live in the four study districts. The study team visited the study districts and collected information regarding the study population from the concerned stakeholders at the district and VDC level. At each location, information on population size was collected by direct and indirect counting. Wives of migrant laborers were then aggregated to arrive at a total number. After estimating their number in different locations, these locations were divided into clusters. A VDC with at least 30 wives of migrant laborers was defined as a cluster. Thirty clusters were selected from the four study districts using the probability proportional to size (pps) method. The study team then visited the ward of each VDC in the selected cluster and identified the wives of migrant laborers living in each ward during actual field survey. They held discussions with local people, FCHVs, women's groups, health workers, shop owners, teachers, community leaders and families of migrants to update the list. In the next stage, 13/14 respondents were randomly selected from each cluster. Laboratories/clinics were set up in each selected cluster to collect blood samples to test for HIV as well as to carry out physical examinations for STI symptoms. After obtaining informed consent, a questionnaire on participants' socio-demographic and HIV-risk behavior information was administered by trained interviewers. Blood samples were then collected in 3-5 capillary tubes by finger-prick, a staff nurse performed an examination, and treatment was given for any current STI. All study participants were provided with pre-test HIV counseling. The blood samples were analyzed for HIV and on-the spot results were provided at the respective study sites by a trained counselor. Key Findings HIV prevalence among the wives of migrant laborers is estimated to be 3.3 percent, and varies across four districts with 4.5 percent in Achham, 3 percent in Doti, 2.5 percent in Kailali, and 1.1 percent in Kachanpur. HIV prevalence among the respondents is significantly co-related with their marital status. Six of the 15 widow respondents (40%) were HIV positive compared to seven HIV-positive cases among 385 currently married respondents (1.8%). Around two in ten respondents reportedly had at least one STI symptom in the past year (20.5%) and at the time of the survey (17.5%). At the same time, 4.8 percent of respondents said that their husbands had STI symptoms during their last home visit, while 2.7 percent of them mentioned that their spouse had STI symptoms during second last home visit. Overall, 95 percent of the respondents had been married at the age of less than 20 years: this included 27.2 percent of respondents who were married when they were 5-14 years. The majority of respondents (71.5%) were illiterate. Around 93 percent of respondents' spouses had paid at least two home visits after migrating to India. Most of the respondents had sexual contact with their spouses during their last home visit (98.8%) and second last home visit (92.2%). Sex outside marriage appears to be a less common phenomenon among the wives of migrant laborers, with the majority of them (98.5%) denying having such sexual relations. A total of 96.5 percent respondents had ever heard about condoms and also knew about different condom outlets. However, only 27.2 percent of them had ever used a condom. Among those respondents who had sex with their husbands during their last home visit, 5.8 percent (23/395) had consistently used condoms, while only 4.6 percent (17/369) of those respondents who had sex with their husband during their second last home visit had used condoms consistently. Three of the 400 respondents (0.8%) had never heard about HIV/AIDS. Additionally, although 72.5 percent of the respondents who had heard about HIV/AIDS knew about a place where they could go for HIV test, only 12.1 percent had ever taken an HIV test. Seventy-eight percent of the respondents knew all about the 'ABC' ('A' - abstinence from sexual contact; 'B' - monogamy; 'C' - consistent use of condoms), only 18 percent of them were aware of all of 'BCDEF' ('B' - monogamy; 'C' - consistent use of condoms; 'D' - a healthy looking person may have HIV; 'E' - a person cannot get the HIV virus from a mosquito bite; 'F' -HIV cannot be transmitted while sharing a meal with an HIVpositive person). Overall, 27.5 percent of them had met a peer/outreach educator, 6.3 percent had visited an STI clinic, 7.3 percent had been to a voluntary counseling and testing (VCT) center, 14.3 percent had participated in HIV/AIDS awareness raising programs and 2.3 percent had been visited by a CHBC (community home based care) staff in the past year. This included a relatively higher proportion of respondents from Kanchanpur (45.7%) and Achham (39%) districts than Doti (18.2%) and Kailali (17.5%).